Evaluation of Women’s Knowledge about Risk Factors and Early Detection of Breast Cancer at Ibn Rushd College of Education in Baghdad University - alabbody, Huda; alwan, nada; attoof, wafa; ryad, bydaa (Iraqi National Journal of Nursing Specialties, 2017)
Objective: Evaluation of women’s knowledge about risk factors and early detection of breast cancer at Ibn Rushd college of education in Baghdad University. Methodology: The study sample included (184) women in the Ibn Rushd College / University of Baghdad, whose age ranged between (17-58) years. Data were collected through a structured questionnaire prepared by the National Cancer Research Center which were answered during a scientific symposium about breast cancer. The score was calculated by correcting the results of the answer, giving one score for each correct answer and then estimating the level of knowledge and inputting all data in a statistical program. Results: The results showed limited level of women’s knowledge about risk factors. As good, medium and weak answer ratios of (11%).(21%) and (69%) each, respectively. . The study revealed no significant relationship between the level of knowledge with age, occupation and married status (p < 0.05)). there was more than half of a correct answer to some risk factors such as, increase the probability of disease with age (53%), obesity in postmenopausal (53%) or breast self-examine once a month after the menstrual cycle (69 %,), and more than 60% consent increasing physical activity and good nutrition and maintaining a healthy weight and stay away from abuse hormones, alcohol be able to prevent of breast cancer Recommendations: Promoting public education and awareness campaigns on the risk factors for breast cancer among women in university is mandatory to control the disease